Tax Avoidance and Corporate Social Responsibility in China - Huang, Jiayi (2019)
Abstract It has been several decades since the notion of corporate social responsibility (CSR) was put forward, and the performance of CSR has been discussed by many scholars. In recent years, whether corporate tax avoidance is affected by CSR performance has become a popular topic. Most of these researches are carried out in developed countries with complete capital market and complete tax system. China is a developing country that now pays more and more attention to CSR, and recently China has gradually strengthened supervision on tax avoidance. Moreover, a great ratio of China's listed companies is state-owned which are dominated by the government. Therefore, under the special circumstances, it is worthy of attention of using data of China's listed companies. This paper selects a number of A-share listed companies in China as samples and examines their CSR performance between 2014 and 2018, which includes 3416 observations, to test and analyse the relationship between CSR performance and the degree of tax avoidance. At the same time, this paper also tests and analyses the different influence of CSR on state-owned corporations and non-state-owned corporations. After utilizing descriptive analysis, correlation analysis, regression analysis, and robustness test, the study finds that the higher the CSR score or the better the company's performance, the lower degree of tax avoidance. There was a negative correlation and it was statistically significant. In addition, the test in companies with different ownership finds that CSR has a small impact on tax avoidance behaviours in state-owned corporations but a strong inhibiting effect on tax avoidance behaviours in non-state-owned corporations. Finally, according to the corporate culture theory, stakeholder theory and risk management theory, the reasons for the two results are analysed. This paper provides evidence of China for the empirical research on the CSR performance and the degree of tax avoidance. Keywords: Tax avoidance, Corporate Social Responsibility, Ownership